Responding to domestic violence within the workplace: reflections and recommendations from the DVFREE workplace initiative in Aotearoa New Zealand. (2nd October 2022) - Carrington, Holly; Williamson, Rachel
ABSTRACT: While the world of work has long been juxtaposed against private, domestic spaces, in recent years the line between the two spheres has become increasingly blurred. This is especially the case when considering the relationship between domestic violence and the workplace, which is not only affected by the intrusion of domestic violence into the workplace but compounded by the increasing amount of work conducted from home. These intersections between domestic violence and work have been subject to mounting scrutiny in recent years, resulting in calls for policy changes that acknowledge domestic violence to be a workplace issue and which develop an appropriate employer response accordingly. This article offers a case study of DVFREE, a domestic violence workplace program delivered by specialist domestic violence organisation Shine in Aotearoa New Zealand. DVFREE adopts a systems-approach to instantiate and support structural change within an organisation. We consider the New Zealand specific-context, before offering a series of practice recommendations that address why and how employers can support employees experiencing domestic violence, drawing our conclusions from knowledge gained through the implementation of the DVFREE initiative. This knowledge offers an important, hitherto largely absent, perspective to research in this field, providing much-needed practical steps for employers.